Peningkatan Kemampuan Menulis Puisi dengan Menggunakan Model Pembelajaran Inkuiri pada Siswa Kelas IV MIN 4 Bengkulu Tengah - Izhar, Izhar (UNIB Press, 2017)
The objectives of this research was to know the improving ability of writing poetry by using inquiry teaching model on the fourth grade students of MIN 4 Bengkulu Tengah. This research was an action research done in 2 cycles performed, each cycle was consist of four stages namely: planning, acting, observing, and reflecting. The action research was done in class IV, consist of 21 students, 11 female students, and 10 male students. The data collected by a tes of writing poetry and observation sheet of the effectiveness of students in teaching process. Then, the data analyzed by avarage, percentage, and classification. The results of research showed that the students’ ability of writing poetry increased with average only reached 69,02 with classification “enough” in first cycle became 81,04 in second cycle with classifiation “good”. Based on the result of the research, it can be concluded that there was the improving ability of writing poetry by using inquiry teaching model on the fourth grade students of MIN 4 Bengkulu Tengah.